Maria Cantacuzino (1817 – 1898) (Confluenţe Bibliologice, 2025)
The author presents the chronic of Cantacuzino family with aristocratic military traditions. Maria Cantacuzino was part of a branch of Cantacuzino- Măgureanu -Deleanu of Moldova. Equipped with a special charm, she obtained a special education being directed by her father, who was a man of superior culture. In Chassériau studio in 1856, Maria Cantacuzino  knew the painter Puvis de Chavannes who had to exhibit the great painting  Saint Genevieve, the  Patron Saint of Paris at Salon in 1876., which today decorate the Pantheon.The painting Saint Genevieve reproduce Maria Cantacuzino features.
Keywords: Cantacuzino Maria (1817 – 1898); Pierre Puvis de Chavannes (1824 – 1898)